Risk factors and complications after body‐contouring surgery and the amount of stromal vascular fraction cells found in subcutaneous tissue. Issue 6 (13th October 2019) - Morandi, Evi M.; Ploner, Christian; Wolfram, Dolores; Tasch, Christoph; Dostal, Lucie; Ortner, Felix; Pierer, Gerhard; Verstappen, Ralph
Abstract: Body contouring surgery following massive weight loss is often prone to complications. Subcutaneous adipose tissue is a rich source of stromal vascular fraction (SVF) cells, and moreover it plays an important role in the pathophysiology of obesity, metabolic syndrome, and wound healing. In this retrospective, single‐centred appraisal, complications are examined and correlated with individual SVF numbers in abdominal subcutaneous fat tissue. We analysed whether the weight loss method affected complications. Eighty seven massive weight loss patients undergoing body contouring surgery between 2010 and 2017 were included in the study. In total, 57 cases with at least one complication were recorded (65.5%). Maximum lifetime weight was 109.6 kg (range 48‐184 kg). Half of the complications (50.8%) were minor complications without the need for surgical revision. The mean number of SVF found in the resected tissue was 714 997.63 cells/g fat tissue. We found no statistical difference in complication rates dependent on cell numbers. Smoking ( P = .049) and a high BMI at the time point of surgery ( P = .031) led to significantly more complications. Also, a high resection weight ( P = .057) showed a tendency for impaired wound healing. However, there was no difference in complication rates following body contouring procedures attributable to the method of weight loss in this study.